Design and performance test of a novel UAV air-assisted electrostatic centrifugal spraying system - Hu, Heming; Kaizu, Yutaka; Huang, Jingjing; Furuhashi, Kenichi; Zhang, Hongduo; Xiao, Xu; Li, Ming; Imou, Kenji (International Journal of Agricultural and Biological Engineering, 2022)
In order to improve the deposition and uniformity of the pesticide sprayed by the agricultural spraying drone, this study designed a novel spraying system, combining air-assisted spraying system with electrostatic technology. First, an air-assisted electrostatic centrifugal spray system was designed for agricultural spraying drones, including a shell, a diversion shell, and an electrostatic ring. Then, experiments were conducted to optimize the setting of the main parameters that affect the charge-to-mass ratio, and outdoor spraying experiments were carried out on the spraying effect of the air-assisted electrostatic centrifugal spray system. The results showed the optimum parameters were that the centrifugal rotation speed was 10 000 r/min, the spray pressure was 0.3 MPa, the fan rotation speed was 14 000 r/min, and the electrostatic generator voltage was 9 kV; The optimum charge-to-mass ratio of the spray system was 2.59 mC/kg. The average deposition density of droplets on the collecting platform was 366.1 particles/cm2 on the upper layer, 345.1 particles/cm2 on the middle layer, and 322.5 particles/cm2 on the lower layer. Compared to the results of uncharged droplets on the upper, middle, and lower layers, the average deposition density was increased by 34.9%, 30.4%, and 30.2%, respectively, and the uniformity of the distribution of the droplets at different collection points was better. Keywords: UAV spraying, droplet drift, centrifugal sprayer, air-assisted spraying, electrostatic spraying DOI: 10.25165/j.ijabe.20221505.6891 Citation: Hu H M, Kaizu Y, Huang J J, Furuhashi K, Zhang H D, Xiao X, et al. Design and performance test of a novel UAV air-assisted electrostatic centrifugal spraying system. Int J Agric & Biol Eng, 2022; 15(5): 34–40.